PELATIHAN AKUNTANSI DAN KEWIRAUSAHAAN PADA PONDOK PESANTREN AL-TSANIYYAH SEBAGAI ALTERNATIF PEMBERDAYAAN MASYARAKAT MANDIRI - Zenabia, Tsarina; Sicilia, Mita; Yazid, Abu (Publika Citra Media, 2024)
Research and Community Service (PKM) is one of the manifestations of the Tri Dharma of Higher Education. PKM activities is to foster lecturers in improving their abilities and skills as well as the existence of Pamulang University which is an agent of change in order to provide significant benefits to society. The Unpam Accounting Study Program held PKM at Al-Tsaniyyah Islamic Boarding School in South Tangerang Banten. PKM at Al Tsaniyah Islamic Boarding School is to provide accounting and entrepreneurship training and improve hard skills in the field of digital entrepreneurship and utilization in terms of data collection, use of digital interpreneurship content to students as provisions in their future. The materials of PKM are throughout presentations, discussions and training, at the end of the session to find out the extent to which the material can be absorbed, questions and answers are asked to the students and door prizes are given.